Assessment of mudstone compaction in exploration wells in the Rovuma Basin, offshore Mozambique. Issue 10 (October 2019) - Nhabanga, Oscar J.; Ringrose, Philip S.
Abstract: In order to develop an improved pore pressure prediction model for the overburden mudstones in the Rovuma Basin, offshore Mozambique, we apply Eaton's method to example well data from three exploration wells, which intersect Quaternary, Tertiary and Cretaceous sediments over depth intervals down to ∼3 km below seafloor. The predictive method only included the effects of mechanical compaction, which is a reasonable assumption for the low-temperature shallow sections. We found that Eaton's method applied to resistivity and acoustic log attributes works well and can be used to identify the mudstones that display over-pressured or normally pressured sections. The predicted pore pressures showed a good match to pore pressures in permeable formations. Using this calibration, we derived an improved pore-pressure prediction method for these wells and for the Rovuma Basin in general. The resulting model should give a good basis for future analysis of compaction processes and pore pressure in this basin. Abstract : Geology; Geophysics; Petroleum engineering; Petrology; Lithology; Mineralogy; Mudstone; Rovuma basin; Sonic transit time; Pore pressure; Effective stress; Resistivity